IMPLEMENTASI KURIKULUM IMAN DAN AL-QUR’AN DALAM MEMBENTUK KARAKTER IMANI DI KUTTAB AL-FATIH MALANG - Ayu Al Adawiyah Rohmatun; M. Nurul Humaidi; Muhammad Yusuf (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2023)
The curriculum transition becomes a logical consequence that occurs, basically curriculum changes focus more on the character of students. The curriculum has changed because the challenges are getting stronger, so reforms are carried out so that education in Indonesia develops optimally. Kuttab Al-Fatih Malang is an Islamic educational institution whose mission is to restore the revival of Islam and the glory of knowledge by implementing a faith and Al-Qur'an curriculum based on the Al-Qur'an and sunnah. This study aims to describe the implementation of the faith and Al-Qur'an curriculum at Kuttab Al-Fatih Malang in shaping the faith character of students. Researchers used a type of field research that is qualitative in nature, with data collection techniques in the form of observation, interviews and documents at Kuttab Al-Fatih Malang. The results showed that the implementation at Kuttab Al-Fatih Malang was based on three stages, namely planning, implementation and evaluation. The formation of faith character refers to the concept of a holistic approach developed in learning faith and the Koran, developing daily, weekly, monthly, semester and annual programs for students and educators as well as through good synergy between teachers and parents.